PENDUGAAN STOK IKAN TEMBANG (Sardinella fimbriata) PADA LAUT FLORES (KAB. BULUKUMBA, BANTAENG, JENEPONTO DAN TAKALAR) - Irianis Latupeirissa (AGRICOLA, 2013)
Sardinella fimbriata stock assessment purposes on sea Flores to know the stock, Maximum Sustainable Yield (MSY) and the level of utilization of fish in the sea Flores on Bulukumba, Bantaeng, Jeneponto and Takalar district. The method used is surplus production models, this model uses secondary data analysis of the catch per unit (CPUE) and business units (effort f). Data were analyzed by calculating the F MSY and optimal. Data analysis of fishery production in South Sulawesi province, it can be concluded that the presence of the Sardinella fimbriata population in the sea Flores Bulukumba, Bantaeng, Jeneponto and Takalar district year 1999-2007 has not happened over fishing, sustainable MSY estimated value limit of 10,000 tons per year with an estimated value of f OPT. 1,000,000 trips per year from the data obtained, the production of the highest catches in 2001 is 6256.50 tons